2018
DOI: 10.1111/1750-3841.14403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Hydrolysis with Papain on the Characteristics of Transglutaminase‐Crosslinked Tofu Gel

Abstract: The effects of partial enzymatic hydrolysis of soymilk on the characteristics of transglutaminase (TG)crosslinked tofu gel were studied. SDS-PAGE showed that the molecular weight of the partially hydrolyzed soybean protein was reduced to that of a digested peptide (less than 43.0 kDa) when papain was added at more than 50 μL/100 mL soymilk. The content of free sulfhydryls, β-sheets, and random coils in papain-treated soymilk increased. When TG was added to soy milk after papain treatment and tofu gel was forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) used 15% acrylamide separating gel and 5% acrylamide stacking gel, according to the method described by Li et al. (2018). The gel samples prepared with different concentrations of enzyme preparations were vacuum freeze‐dried.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) used 15% acrylamide separating gel and 5% acrylamide stacking gel, according to the method described by Li et al. (2018). The gel samples prepared with different concentrations of enzyme preparations were vacuum freeze‐dried.…”
Section: Methodsmentioning
confidence: 99%
“…This is a new type of tofu with high gel strength that could be produced using the enzymatic cross-linking of MTGase and an appropriate thermal treatment. However, each type of coagulants used in the traditional tofu production process has its own inherent disadvantages, which are summarized as follows: tofu was typi-cally made using GDL as an acid coagulant, although it is easy to control because it acidifies slowly; the resulting tofu is slightly sour and not suitable for frying due to its soft texture (Li, Wu, et al, 2018). Residual undissolved CS or rapid release of MC in tofu products typically results in poor quality (a coarse texture) (Cao et al, 2017;.…”
Section: Type Of Coagulant and Phmentioning
confidence: 99%
“…They showed that tofu coagulated using papain resulted in higher protein content (9.3%) compared with that of tofu coagulated using CS (6.5%). Independently, Li, Wu, et al (2018) studied the effect of papain-pretreated soymilk on Transglutaminase (TG)-cross-linked tofu products. The quality of tofu products (in terms of strength, WHC, and nonfreezing water content) was better than tofu products without enzyme treatment.…”
Section: New Coagulantmentioning
confidence: 99%
See 2 more Smart Citations